Pemanfaatan Media Sosial Sebagai Sarana Promosi Dalam Meningkatkan Jumlah Pengunjung Di Pantai Ngurbloat Maluku Tenggara - Jalmaf, Abraham Johanis; Sahusilawane, Stevie; Rehatta, Geradin (Jurnal Administrasi Terapan, 2022)
This study aims to find out an in-depth picture which uses social media as a means of tourism promotion in the Ngurbloat coastal tourist area of Ngilngof Village. The sample in this study was 6 people on Ngurbloat beach. The data collection technique was interviews, data analysis techniques were data reduction, data presentation, and conclusion drawing or verification. The results showed that utilizing social media as a promotional media at Ngurbloat Beach, is a complete feature of social media, in the process of displaying products (Ngurblaot beach) to prospective customers / tourists and social media is very cost-effective in carrying out a promotion. visitors who know about Ngurbloat Beach and come to Ngurbloat Beach to enjoy tourist services and facilities at Ngurbloat Beach.Keywords: Social Media, Promotion.